Safeguard of the Police Intelligence Against Court Decisions Regarding the Object of the Dispute - La Ode Husen; Salle Salle; Arri Abdi Syalman; Abd. Kahar Muzakkir (Sovereign: International Journal of Law, 2020)
This study aims to analyze the effectiveness of safeguard of the Police Intelligence against court decisions regarding the object of the dispute in South Sulawesi Province. This research uses an empirical study method which is also called sociological legal research because it sees the application of law as a factual condition in the social environment and its relationship with legal norms. This research was conducted in South Sulawesi Province, with 92 respondents. Data analysis in this study uses a qualitative approach, which processes the output of the questionnaire, and is presented in the form of frequency tabulation (F) and percentage distribution (%). The results of this study show that the safeguard of South Sulawesi Regional Police Ditintelkam in the execution process regarding the object of the dispute in South Sulawesi Province based on Perkap BIN No. 2 of 2013, can be assessed from four aspects, as follows: Safeguarding Targets; Safeguarding Implementation; Coordination and Administration; and Supervision and Controlling. Data acquisition of all indicators based on safeguard aspects of the South Sulawesi Regional Police Ditintelkam still shows less effective results. Seriousness is needed in increasing the safeguard effectiveness at the South Sulawesi Regional Police Ditintelkam to ensure the process of executing court decisions regarding the object of the dispute can be more effective in the future.